2002
DOI: 10.1021/np010621l
|View full text |Cite
|
Sign up to set email alerts
|

Carvone and Perillaldehyde Interfere with the Serum-Induced Formation of Filamentous Structures inCandidaalbicansat Substantially Lower Concentrations than Those Causing Significant Inhibition of Growth

Abstract: Carvone and perillaldehyde were shown to inhibit the transformation of Candida albicans to a filamentous form at concentrations far lower and more biologically relevant than the concentrations necessary to inhibit growth. This morphological transformation is associated with C. albicans pathogenicity; hence these naturally occurring monoterpenes are potential lead compounds in the development of therapeutic agents against C. albicans infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 11 publications
(13 reference statements)
2
28
0
1
Order By: Relevance
“…143 A similar observation is reported from perillaldehyde (79) and carvone (83), which both inhibit the transformation of Candida to the filamentous form at concentrations far lower than the growth inhibitory concentration. 190 Sesquiterpene inhibitors can be attributed to the compound groups of hydrocarbons (90,91), alcohols (92-96, 100, 103), bisabolan type compounds (100-103), phenols (98-101), dialdehydes (105)(106)(107), and lactones (108)(109)(110)(111)(112) having an exocyclic double bound as shown in Figure 3. A difference in the mechanisms of antimicrobial and mutagenic activity has been demonstrated by the example of dialdehydes, 191 of which polygodial (107) turned out to be as an antifungal, nonmutagenic compound.…”
Section: E Vapor Phase Activity Testsmentioning
confidence: 99%
“…143 A similar observation is reported from perillaldehyde (79) and carvone (83), which both inhibit the transformation of Candida to the filamentous form at concentrations far lower than the growth inhibitory concentration. 190 Sesquiterpene inhibitors can be attributed to the compound groups of hydrocarbons (90,91), alcohols (92-96, 100, 103), bisabolan type compounds (100-103), phenols (98-101), dialdehydes (105)(106)(107), and lactones (108)(109)(110)(111)(112) having an exocyclic double bound as shown in Figure 3. A difference in the mechanisms of antimicrobial and mutagenic activity has been demonstrated by the example of dialdehydes, 191 of which polygodial (107) turned out to be as an antifungal, nonmutagenic compound.…”
Section: E Vapor Phase Activity Testsmentioning
confidence: 99%
“…Several categories of natural products and synthetic chemicals have been screened and evaluated for their efficacy against C. albicans adhesion and morphological transition in recent years. Carvone and perillaldehyde were found to inhibit the formation of C. albicans filamentous structures (McGeady et al ., 2002). Quorum sensing molecules such as farnesoic acid and cis ‐2‐dodecenoic acid (BDSF) inhibit C. albicans hyphae formation and appear to play a key role in regulating the C. albicans morphological transition (Oh et al ., 2001; Kim et al ., 2002; Boon et al ., 2008; Deng et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that Candida infections are usually difficult to eradicate completely in patients receiving antifungal agents continuously for long periods of time [20] [21]. Furthermore, it has been reported that C. parapsilosis, C. tropicalis, and C. glabrata infections have become more common in recent years [22].…”
mentioning
confidence: 99%